Resin particles

CN115124768BActive Publication Date: 2026-10-27FUJIFILM BUSINESS INNOVATION CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202111452666.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2021-12-01
Publication Date
2026-10-27
Estimated Expiration
2041-12-01

AI Technical Summary

Benefits of technology

[0027]根据<1>所涉及的发明,提供一种与在具有含有生物可降解性树脂及增塑剂的母粒子的树脂粒子中,通过X射线荧光分析求出的离子价数可能会成为2以上的金属元素的量相对于树脂粒子总量小于0.002质量%或超过2.0质量%的情况相比,维持灵活性并且在高温条件下长期保管时的渗出得到抑制的树脂粒子。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003385608210000071
    Figure BDA0003385608210000071
  • Figure BDA0003385608210000101
    Figure BDA0003385608210000101
  • Figure BDA0003385608210000111
    Figure BDA0003385608210000111
Patent Text Reader

Abstract

A resin particle having a parent particle containing a biodegradable resin and a plasticizer, wherein the amount of a metal element whose ionic valence can be 2 or more, as determined by X-ray fluorescence analysis, is 0.002 mass% or more and 2.0 mass% or less with respect to the total amount of the resin particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a resin particle. Background Technology

[0002] Patent document 1 discloses "a biodegradable resin composition, characterized in that it comprises a recalcitrant biodegradable resin (A), polyglycolic acid (B), and an ester decomposition promoter (C) composed of inorganic particles that promotes the hydrolysis of the polyglycolic acid."

[0003] Patent document 2 proposes "a method for manufacturing coated particles with a layer composed of calcium phosphate to coat the surface, characterized in that resin particles with an average particle size of 0.01 μm or more and 1,000 μm or less are dispersed or impregnated in an aqueous solution containing Ca ions and phosphate ions for more than 12 hours at a temperature of 30°C or above."

[0004] Patent Document 1: Japanese Patent Application Publication No. 2012-077245

[0005] Patent Document 2: Japanese Patent Application Publication No. 2004-210848 Summary of the Invention

[0006] The objective of this invention is to provide a resin particle that maintains flexibility and suppresses the leaching of plasticizer from the resin particle during long-term storage at high temperatures, compared to cases where, in resin particles containing parent particles of biodegradable resin and plasticizer, the amount of metal elements whose ionic valence number, as determined by X-ray fluorescence analysis, may be 2 or higher, is less than 0.002% by mass or more than 2.0% by mass relative to the total amount of resin particles; the ratio of the circumference equivalent diameter Rs of the aggregate to the circumference equivalent diameter Rp of the primary particle (Rs / Rp) is 1.5 or higher after storage for three months at 50°C and 50% RH; or the indicated hardness is 75 or higher. (Hereinafter, the phenomenon of "plasticizer leaching from resin particles" is sometimes referred to as "leaching".)

[0007] The above-mentioned problem was solved through the following solution. That is,

[0008] <1> A resin particle having a parent particle containing a biodegradable resin and a plasticizer, wherein,

[0009] The amount of metal elements with ion valences greater than 2 determined by X-ray fluorescence analysis is greater than 0.002% by mass and less than 2.0% by mass relative to the total amount of resin particles.

[0010] <2> According to the resin particles described in <1>, wherein,

[0011] The metal element whose ionic valence may be 2 or higher includes at least one selected from the group consisting of Ca, Mg, Al and Fe.

[0012] <3> According to the resin particles described in <2>, wherein,

[0013] The ion valence may be 2 or higher for metallic elements, including Ca.

[0014] <4> The resin particles according to any one of <1> to <3>, wherein,

[0015] The biodegradable resin is a cellulose acylated resin.

[0016] <5> According to the resin particles described in <4>, wherein,

[0017] The cellulose acylate is at least one selected from the group consisting of cellulose diacetate, cellulose acetate propionate, and cellulose acetate butyrate.

[0018] <6> According to the resin particles described in <1> to <5>, wherein,

[0019] The ratio (B / A) of the content of the plasticizer (B) to the content of the biodegradable resin (A) is 0.1 or more and 0.8 or less.

[0020] <7> A resin particle having a parent particle containing a biodegradable resin and a plasticizer, wherein,

[0021] After being stored at 50℃ and 50% RH for three months, the ratio of the equivalent circular diameter Rs of the aggregates to the equivalent circular diameter Rp of the primary particles (Rs / Rp) is less than 1.5.

[0022] The hardness is less than 75.

[0023] <8> The resin particles according to any one of <1> to <7> have, in sequence, the following on the surface of the parent particle:

[0024] The first layer comprises at least one cationic resin selected from polyalkyleneimide, polyacrylamide, and polyethyleneimine; and

[0025] The second layer contains anionic or nonionic hydrophilic compounds.

[0026] Invention Effects

[0027] According to the invention described in <1>, a resin particle is provided in which the amount of a metal element whose ionic valence, as determined by X-ray fluorescence analysis, may be 2 or higher relative to the total amount of the resin particle is less than 0.002% by mass or more than 2.0% by mass, maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to a case where the amount of the metal element in the resin particle containing a parent particle containing a biodegradable resin and a plasticizer is less than 0.002% by mass or more relative to the total amount of the resin particle.

[0028] According to the invention described in <2>, a resin particle is provided that maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to cases where the metal element whose ionic valence may be 2 or higher includes Ba other than Ca, Mg, Al and Fe.

[0029] According to the invention described in <3>, a resin particle is provided that maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to a case where the metal element whose ionic valence may be 2 or higher does not contain Ca but contains at least one selected from the group consisting of Mg, Al and Fe.

[0030] According to the invention described in <4>, a resin particle is provided that maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to the case where the biodegradable resin is polyester.

[0031] According to the invention described in <5>, a resin particle is provided that maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to the case where the cellulose acylate is cellulose triacetate.

[0032] According to the invention described in <6>, a resin particle is provided that maintains flexibility and suppresses exudation during long-term storage at high temperatures, compared to a plasticizer content (B) to a biodegradable resin content (A) ratio (B / A) of less than 0.1 or more than 0.8.

[0033] According to the invention described in <7>, a resin particle is provided that, compared with the case where the ratio of the spherical equivalent diameter Rs of the aggregate to the spherical equivalent diameter Rp of the primary particle (Rs / Rp) of the resin particles having a master particle containing a biodegradable resin and a plasticizer is 1.5 or more after being stored for three months at 50°C and 50% RH, or the indicated hardness is 75 or more, maintains flexibility and suppresses exudation during long-term storage at high temperatures.

[0034] According to the invention described in <8>, a resin particle is provided that, compared with resin particles having a parent particle containing a biodegradable resin and a plasticizer, and in which the amount of a metal element whose ionic valence, as determined by X-ray fluorescence analysis, may be 2 or more, is 0.002% by mass or more and 2.0% by mass or less relative to the total amount of resin particles, or in which the ratio of the circumstable equivalent diameter Rs of the aggregate to the circumstable equivalent diameter Rp of the primary particle (Rs / Rp) is less than 1.5 and the indicated hardness is less than 75, the parent particle does not have a first layer containing at least one cationic resin of polyalkyleneimide, polyacrylamide, and polyethyleneamine and a second layer containing anionic or nonionic hydrophobic compounds on its surface, maintaining flexibility and suppressing exudation during long-term storage at high temperatures. Detailed Implementation

[0035] The following describes one example, or embodiment, of the present invention. These descriptions and examples are illustrative and do not limit the scope of the invention.

[0036] Within the numerical ranges described in this specification, the upper or lower limit value described as a single numerical range can be replaced with the upper or lower limit value of other numerical ranges described in different stages. Furthermore, within the numerical ranges described in this specification, the upper or lower limit value of the numerical range can be replaced with the values ​​shown in the embodiments.

[0037] Each component may contain multiple corresponding substances.

[0038] When referring to the amount of each component in a composition, if a plurality of substances corresponding to each component are present in the composition, it indicates the total amount of such plurality of substances present in the composition unless otherwise specified.

[0039] In this specification, the term "process" is included not only in an independent process, but also when the desired purpose of the process cannot be clearly distinguished from other processes.

[0040] <Resin Particles>

[0041] The resin particles according to the first embodiment have parent particles containing biodegradable resin and plasticizer, and the amount of a metal element whose ionic valence may be 2 or more as determined by X-ray fluorescence analysis (hereinafter, "metal element whose ionic valence may be 2 or more" is also referred to as "specific metal element") is 0.002% by mass or more and 2.0% by mass or less relative to the total amount of resin particles.

[0042] Based on the above structure, the resin particles involved in the first embodiment maintain flexibility and exudation is suppressed during long-term storage at high temperatures. The reasons are explained below.

[0043] Adding plasticizers is very effective in improving the flexibility of resin particles containing biodegradable resins (hereinafter referred to as biodegradable resin particles). However, when biodegradable resin particles containing plasticizers are stored for a long time under high temperature conditions, exudation is likely to occur, which may lead to the aggregation of biodegradable resin particles.

[0044] In the resin particles according to the first embodiment, the amount of a specific metal element, as determined by X-ray fluorescence analysis, is 0.002% by mass or more and 2.0% by mass or less relative to the total amount of resin particles. This specific metal element readily bonds to functional groups (e.g., hydroxyl, carboxyl, etc.) present in biodegradable resins. Therefore, the specific metal element readily forms a cross-linked structure with the biodegradable resin. Consequently, the exudation of plasticizers contained in the resin particles is suppressed. Furthermore, by setting the amount of the specific metal element within the aforementioned range, a greater number of such cross-linked structures are present without compromising the flexibility of the resin particles.

[0045] Therefore, it is estimated that the resin particles involved in the first embodiment maintain flexibility and that exudation is suppressed during long-term storage under high temperature conditions.

[0046] The resin particles involved in the second embodiment have parent particles containing biodegradable resin and plasticizer.

[0047] Furthermore, after being stored at 50°C and 50% RH for three months, the ratio of the circular equivalent diameter Rs of the aggregate to the circular equivalent diameter Rp of the primary particle (Rs / Rp) is less than 1.5.

[0048] Moreover, the measured hardness is less than 75.

[0049] Here, "aggregate" refers to a secondary particle formed by the aggregation of two or more primary particles, i.e., resin particles.

[0050] Based on the above structure, the resin particles involved in the second embodiment maintain flexibility and exudation is suppressed during long-term storage at high temperatures. The reasons are explained below.

[0051] The ratio (Rs / Rp) of the spherical equivalent diameter Rs of the aggregates of resin particles according to the second embodiment after storage at 50°C and 50% RH for three months is less than 1.5. A ratio (Rs / Rp) less than 1.5 indicates that primary particle aggregation is less likely to occur even under long-term storage at high temperatures. Aggregation of primary particles in resin particles containing plasticizers stored at high temperatures for extended periods tends to be caused by the exudation of plasticizers from the resin particles. In other words, a ratio (Rs / Rp) less than 1.5 indicates that exudation is suppressed even under long-term storage at high temperatures.

[0052] Furthermore, the resin particles involved in the second embodiment have a hardness of less than 75 and are flexible.

[0053] Therefore, it is estimated that the resin particles involved in the second embodiment maintain flexibility and that exudation is suppressed during long-term storage under high temperature conditions.

[0054] Hereinafter, resin particles corresponding to the resin particles involved in the first or second embodiment will be described in detail. However, any example of the resin particles of the present invention may be any resin particle corresponding to any one of the resin particles involved in the first or second embodiment.

[0055] (mother particle)

[0056] -Biodegradable resin-

[0057] The parent particles contain biodegradable resin.

[0058] Parent particles may include particles that contain biodegradable resin as the main component, specifically particles that contain 90%, 95%, 98%, or 100% biodegradable resin relative to the total amount of parent particles.

[0059] Here, biodegradable resin refers to resin that is broken down into water and carbon dioxide by microorganisms. Specifically, biodegradable resin is defined as resin whose aerobic biodegradation rate, measured using a method based on ISO-14855-2 (2018), is greater than 50% within one month.

[0060] Examples of biodegradable resins include cellulose acylates, polyesters, and natural polymers.

[0061] Cellulose acylated products are cellulose derivatives in which at least a portion of the hydroxyl groups in cellulose are replaced (acylated) by acyl groups. The acyl group has a -CO-R group. AC (R ACA group representing a hydrogen atom or a hydrocarbon group. Examples of cellulose acylates include cellulose derivatives represented by the general formula (CA).

[0062] Examples of polyesters include aliphatic polyesters and aliphatic aromatic polyesters.

[0063] Examples of aliphatic polyesters include polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), polycaprolactone, polybutylene succinate (PBS), polybutylene succinate / adipate (PBSA), and polyethylene glycol succinate (PBA), among other polyhydroxy fatty acid esters.

[0064] Examples of aliphatic aromatic polyesters include polybutylene adipate / terephthalate copolymer resin (PBAH) and polytetramethylene adipate / terephthalate copolymer resin.

[0065] Examples of natural macromolecules include starch, cellulose, chitin, chitosan, gluten, gelatin, casein, soy protein, collagen, and keratin.

[0066] As a biodegradable resin, cellulose acylates are preferred, for example.

[0067] Cellulose acylates have hydroxyl groups in their main chain, thus increasing the number of sites for bonding with specific metal elements. Consequently, the cross-linking structure with specific metal elements is more readily formed, thereby further suppressing the exudation of plasticizers.

[0068] Cellulose acylates

[0069] Cellulose acylated compounds are, for example, cellulose derivatives represented by the following general formula (CA).

[0070] [Chemical Formula 1]

[0071]

[0072] In the general formula (CA), A1, A2, and A3 independently represent hydrogen atoms or acyl groups, and n represents an integer greater than 2. At least some of the n A1, n A2, and n A3 atoms represent acyl groups. The n A1 atoms in a molecule can be all identical, partially identical, or different from each other. Similarly, the n A2 atoms and n A3 atoms in a molecule can be all identical, partially identical, or different from each other.

[0073] In the acyl groups represented by A1, A2 and A3, the hydrocarbon group in the acyl group can be any one of straight chain, branched chain and cyclic, but is preferably straight chain or branched chain, and more preferably straight chain.

[0074] In the acyl groups represented by A1, A2 and A3, the hydrocarbon group in the acyl group can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, but is more preferably a saturated hydrocarbon group, for example.

[0075] The acyl groups represented by A1, A2, and A3 are preferably acyl groups with one or more but no more than six carbon atoms. That is, as a cellulose acylated product, a cellulose acylated product with one or more but no more than six carbon atoms in the acyl group is preferred.

[0076] In the acyl groups represented by A1, A2, and A3, the hydrogen atom in the acyl group can be replaced by a halogen atom (e.g., a fluorine atom, a bromine atom, an iodine atom), an oxygen atom, a nitrogen atom, etc., but is preferably unsubstituted.

[0077] Examples of acyl groups represented by A1, A2, and A3 include formyl, acetyl, propionyl, butyryl, acryloyl, and hexanoyl. From the viewpoint of improving the biodegradation rate of resin particles, acyl groups with two or more but less than four carbon atoms are more preferred, and those with two or three carbon atoms are even more preferred.

[0078] Examples of cellulose acylates include cellulose acetate (cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).

[0079] From the viewpoint of improving the biodegradation rate of resin particles, cellulose acylates are preferably, for example, cellulose acylates having two or more acyl groups. Specifically, as cellulose acylates, from the viewpoint of improving the biodegradation rate of resin particles, cellulose diacetate, cellulose propionate (CAP), and cellulose acetate butyrate (CAB) are preferred, and cellulose propionate (CAP) is more preferred.

[0080] As a cellulose acylated compound, the number of hydroxyl groups in the main chain of at least one selected from the group consisting of cellulose diacetate, cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB) is a more suitable range, and it is easier to obtain resin particles with a cross-linked structure within a range that does not impair the flexibility of the resin particles. Therefore, it is easier to obtain resin particles that maintain flexibility and suppress exudation during long-term storage under high-temperature conditions.

[0081] Cellulose acylates can be used alone or in combination with two or more.

[0082] The weight-average degree of polymerization of the cellulose acylate is preferably 200 or more and 1000 or less, more preferably 500 or more and 1000 or less, and even more preferably 600 or more and 1000 or less.

[0083] The weight-average degree of polymerization of cellulose acylates is determined from the weight-average molecular weight (Mw) in the following order.

[0084] First, the weight-average molecular weight (Mw) of cellulose acylates was measured using tetrahydrofuran and by gel permeation chromatography (GPC apparatus: TOSOHCORPORATION, HLC-8320GPC, column: TSKgelα-M) to polystyrene conversion.

[0085] Next, the degree of polymerization of the cellulose acylate is determined by dividing by the molecular weight of the structural unit. For example, when the substituent of the cellulose acylate is acetyl, the molecular weight of the structural unit is 263 when the degree of substitution is 2.4, and 284 when the degree of substitution is 2.9.

[0086] From the viewpoint of improving the biodegradation rate of resin particles, the degree of substitution of cellulose acylate is preferably 2.1 or more and 2.9 or less, more preferably 2.2 or more and 2.9 or less, even more preferably 2.3 or more and 2.9 or less, and especially preferably 2.6 or more and 2.9 or less.

[0087] From the viewpoint of improving the biodegradation rate of resin particles, in cellulose acetate propionate (CAP), the ratio of the degree of substitution of acetyl groups to propionyl groups (acetyl / propionyl) is preferably 0.01 or more and 1 or less, more preferably 0.05 or more and 0.1 or less.

[0088] From the viewpoint of improving the biodegradation rate of resin particles, in cellulose acetate butyrate (CAB), the ratio of the degree of substitution of acetyl groups to butyryl groups (acetyl / butyryl) is preferably 0.05 or more and 3.5 or less, more preferably 0.5 or more and 3.0 or less.

[0089] The degree of substitution of cellulose acylates refers to the extent to which the hydroxyl groups of cellulose are replaced by acyl groups. In other words, the degree of substitution becomes an indicator of the degree of acylation of cellulose acylates. Specifically, the degree of substitution represents the intramolecular average number of substitutions in the D-pyranose units of cellulose acylates where three hydroxyl groups are replaced by acyl groups. The degree of substitution is determined by the integral ratio of the peak values ​​of hydrogen from cellulose to hydrogen from acyl groups using 1H-NMR (prepared by JMN-ECA / JEOL RESONANCE).

[0090] These biodegradable resins can be used alone or in combination.

[0091] -Plasticizer-

[0092] The parent material contains plasticizers.

[0093] Examples of plasticizers include ester compounds, cashew nut compounds, camphor, metal soaps, polyols, and polyepoxides. From the viewpoint of improving the mechanical properties of resin particles, at least one of ester compounds and cashew nut compounds is preferred as a plasticizer. Furthermore, a single plasticizer or two or more plasticizers can be used in combination.

[0094] Examples of ester compounds include fatty acid esters (adipate esters, citrate esters, sebate esters, azelaate esters, phthalate esters, acetate esters), phosphate esters, condensed phosphate esters, ethylene glycol esters (e.g., ethylene glycol benzoate), and modified fatty acid esters (e.g., epoxidized fatty acid esters). Examples of the aforementioned esters include monoesters, diesters, triesters, and polyesters. Among these, dicarboxylic acid diesters (adipate diesters, sebate diesters, azelaate diesters, phthalate diesters, etc.) are preferred, for example.

[0095] As a plasticizer, it is preferably selected from at least one of the group consisting of adipate, citrate, and sebacic acid ester. Adipate, citrate, and sebacic acid ester have high compatibility with cellulose acylates and disperse cellulose acylates in a nearly uniform manner, thereby further improving thermal fluidity compared to other plasticizers.

[0096] As an adipic acid ester, a mixture of the adipic acid ester with other ingredients can be used. Commercially available examples of such mixtures include Daifatty 101 manufactured by DAIHACHI CHEMICAL INDUSTRY CO.,LTD.

[0097] Examples of fatty acid esters, such as citrate, sebacic acid ester, azelaic acid ester, phthalate, and acetate, include esters of fatty acids and alcohols. Examples of alcohols include monohydric alcohols such as methanol, ethanol, propanol, butanol, and 2-ethylhexanol; and polyhydric alcohols such as glycerol, polyglycerol (diglycerol, etc.), pentaerythritol, ethylene glycol, diethylene glycol, propylene glycol, butanediol, trimethylolpropane, trimethylolethane, and sugar alcohols.

[0098] Ethylene glycol, as a component of ethylene glycol benzoate, can be exemplified by ethylene glycol, diethylene glycol, propylene glycol, etc.

[0099] Epoxidized fatty acid esters are ester compounds having a structure in which the carbon-carbon unsaturated bonds of an unsaturated fatty acid ester are epoxidized (i.e., oxadiol). Examples of epoxidized fatty acid esters include esters of fatty acids and alcohols in which some or all of the carbon-carbon unsaturated bonds in unsaturated fatty acids (e.g., oleic acid, palmitoleic acid, isoleic acid, linoleic acid, linolenic acid, nervonic acid, etc.) are epoxidized. Examples of alcohols include monohydric alcohols such as methanol, ethanol, propanol, butanol, and 2-ethylhexanol; and polyhydric alcohols such as glycerol, polyglycerols (diglycerol, etc.), pentaerythritol, ethylene glycol, diethylene glycol, propylene glycol, butanediol, trimethylolpropane, trimethylolethane, and sugar alcohols.

[0100] The molecular weight (or weight-average molecular weight) of the ester compound used as a plasticizer is preferably 200 or more and 2000 or less, more preferably 250 or more and 1500 or less, and even more preferably 280 or more and 1000 or less. Unless otherwise specified, the weight-average molecular weight of the ester compound is the value measured in accordance with the method for measuring the weight-average molecular weight of cellulose acylates.

[0101] Cashew phenol compounds are preferred as plasticizers, for example.

[0102] Cashew phenol compounds refer to components contained in natural compounds derived from cashew trees (e.g., compounds represented by the following structural formulas (b-1) to (b-4)) or derivatives of said components.

[0103] [Chemical Formula 2]

[0104]

[0105] Cashew phenol compounds can be mixtures of naturally derived compounds made from the cashew tree (hereinafter also referred to as "cashew tree-derived mixtures").

[0106] Cashew phenol compounds can also be derivatives derived from mixtures derived from the cashew tree. Examples of derivatives derived from mixtures derived from the cashew tree include the following mixtures or monomers.

[0107] • A mixture in which the proportions of each component in a blend derived from cashew trees have been adjusted.

[0108] • Monomers from which specific components were isolated from a mixture derived from cashew trees

[0109] • A mixture containing modified compounds derived from cashew trees.

[0110] • A mixture containing polymers that aggregate components derived from cashew trees.

[0111] • A mixture containing modified polymers that modify and polymerize components derived from cashew trees.

[0112] • A mixture containing a modified body that further modifies the components in the mixture with the adjusted composition ratio.

[0113] • A mixture containing polymers from which components in a mixture with adjusted composition ratios are further polymerized.

[0114] • A mixture comprising modified polymers that further modify and polymerize the components in the mixture with the adjusted composition ratio.

[0115] • Modified forms obtained by further modifying the separated monomers

[0116] • Polymers obtained by further polymerization of the separated monomers

[0117] • Modified polymers obtained by further modifying and polymerizing the separated monomers.

[0118] Here, it is assumed that the monomer also contains polymers such as dimers and trimers.

[0119] From the viewpoint of improving the biodegradation rate of resin particles, cashew phenol compounds are preferably, for example, compounds represented by general formula (CDN1) and at least one compound selected from the group consisting of compounds polymerized from compounds represented by general formula (CDN1).

[0120] [Chemical Formula 3]

[0121]

[0122] In the general formula (CDN1), R 1 R represents an alkyl group that may have substituents or an unsaturated aliphatic group that has a double bond and may have substituents. 2 This indicates a hydroxyl group, a carboxyl group, an alkyl group that may have substituents, or an unsaturated aliphatic group that has a double bond and may have substituents. P2 represents an integer greater than or equal to 0 and less than 4. When P2 is 2 or greater, there are multiple R groups. 2 They can be the same group or different groups.

[0123] In the general formula (CDN1), R 1 The alkyl group that may have substituents is preferably an alkyl group with 3 or more and 30 or less carbon atoms, more preferably an alkyl group with 5 or more and 25 or less carbon atoms, and even more preferably an alkyl group with 8 or more and 20 or less carbon atoms.

[0124] Examples of substituents include hydroxyl groups; substituents containing ether bonds such as epoxy and methoxy groups; and substituents containing ester bonds such as acetyl and propionyl groups.

[0125] Examples of alkyl groups that may have substituents include pentadecane-1-yl, heptane-1-yl, octane-1-yl, nonanane-1-yl, decane-1-yl, undecane-1-yl, dodecane-1-yl, tetradecane-1-yl, etc.

[0126] In the general formula (CDN1), R 1 The unsaturated aliphatic group having double bonds and substituents is preferably an unsaturated aliphatic group with 3 or more and 30 or less carbon atoms, more preferably an unsaturated aliphatic group with 5 or more and 25 or less carbon atoms, and even more preferably an unsaturated aliphatic group with 8 or more and 20 or less carbon atoms.

[0127] The number of double bonds in the unsaturated aliphatic group is preferably one or more and three or less.

[0128] As substituents, examples of substituents that are substituents of the alkyl group can also be cited.

[0129] Examples of unsaturated aliphatic groups that have double bonds and may have substituents include pentadecane-8-en-1-yl, pentadecane-8,11-dien-1-yl, pentadecane-8,11,14-trien-1-yl, pentadecane-7-en-1-yl, pentadecane-7,10-dien-1-yl, and pentadecane-7,10,14-trien-1-yl.

[0130] In the general formula (CDN1), as R 1 For example, pentadecane-8-en-1-yl, pentadecane-8,11-dien-1-yl, pentadecane-8,11,14-trien-1-yl, pentadecane-7-en-1-yl, pentadecane-7,10-dien-1-yl, and pentadecane-7,10,14-trien-1-yl are preferred.

[0131] In the general formula (CDN1), as R 2 The alkyl groups that may have substituents and the unsaturated aliphatic groups that have double bonds and may have substituents, as represented by R, can also be exemplified by R. 1 Examples of preferred embodiments are alkyl groups that may have substituents and unsaturated aliphatic groups that have double bonds and may have substituents.

[0132] The compound represented by the general formula (CDN1) can be further modified. For example, it can be epoxidized. From the viewpoint of improving the biodegradation rate of resin particles, in particular, it is preferred, for example, to be a compound represented by the general formula (CDN1) in which the hydroxyl groups are replaced with the following group (EP), i.e., a compound represented by the following general formula (CDN1-e).

[0133] [Chemical Formula 4]

[0134]

[0135] In the group (EP) and general formula (CDN1-e), L EP Represents a single bond or a divalent linkage group. In the general formula (CDN1-e), R 1 R 2 And P2 and R in general formula (CDN1) 1 R 2 P2 has the same meaning.

[0136] In the group (EP) and general formula (CDN1-e), as L EP Examples of divalent linking groups include alkylene groups that may have substituents (preferably alkylene groups with 1 or more but less than 4 carbon atoms, more preferably alkylene groups with 1 carbon atom), -CH2CH2OCH2CH2- groups, etc.

[0137] As a substituent mentioned above, another example can be found in R of the general formula (CDN1). 1 Substituents listed in the table are substituents.

[0138] As L EP For example, methylene is preferred.

[0139] A polymer of compounds represented by general formula (CDN1) is a polymer of at least two compounds represented by general formula (CDN1) polymerized, with or without the use of linking groups.

[0140] As a polymer of a compound represented by the general formula (CDN1), for example, a compound represented by the general formula (CDN2) can be cited.

[0141] [Chemical Formula 5]

[0142]

[0143] In the general formula (CDN2), R 11 R 12 and R 13 Each can be independently represented as an alkyl group that may have substituents or an unsaturated aliphatic group that has a double bond and may have substituents. R 21 R22 and R 23 Each group independently represents a hydroxyl group, a carboxyl group, an alkyl group that may have substituents, or an unsaturated aliphatic group that has a double bond and may have substituents. P21 and P23 independently represent integers greater than or equal to 0 and less than 3, and P22 represents an integer greater than or equal to 0 and less than 2. L 1 and L 2 Each of these groups independently represents a divalent linker. n represents an integer greater than 0 and less than 10. When P21 is greater than 2, there exist a complex number of R groups. 21 When P22 is 2 or more, there exist a complex number of R. 22 And when P23 is 2 or more, there exist multiple R's. 23 They can be the same or different. When n is 2 or more, there exist a complex number of R. 12 R 22 and L 1 They can be the same group or different groups. When n is 2 or more, there are multiple P22s, which can be the same number or different numbers.

[0144] In the general formula (CDN2), as R 11 R 12 R 13 R 21 R 22 and R 23 The alkyl groups that may have substituents and the unsaturated aliphatic groups that have double bonds and may have substituents, as exemplified by R as a general formula (CDN1), are also mentioned. 1 The examples listed here are preferred examples.

[0145] In the general formula (CDN2), L is used as 1 and L 2 The divalent linking group represented can be, for example, an alkylene group that may have substituents (preferably an alkylene group with 2 or more and 30 or less carbon atoms, more preferably an alkylene group with 5 or more and 20 or less carbon atoms).

[0146] As a substituent mentioned above, another example can be found in R of the general formula (CDN1). 1 Substituents listed in the table are substituents.

[0147] In the general formula (CDN2), n is preferably 1 or more and 10 or less, and more preferably 1 or more and 5 or less.

[0148] Compounds represented by the general formula (CDN2) can be further modified. For example, they can be epoxidized, specifically, compounds with the structure of having hydroxyl groups replaced by groups (EP) in compounds represented by the general formula (CDN2), i.e., compounds represented by the following general formula (CDN2-e).

[0149] [Chemical Formula 6]

[0150]

[0151] In the general formula (CDN2-e), R 11 R 12 R 13 R 21 R 22 R 23 P21, P22, P23, L 1 L 2 and n are respectively related to R in the general formula (CDN2) 11 R 12 R 13 R 21 R 22 R 23 P21, P22, P23, L 1 L 2 The meanings of "and n" are the same.

[0152] In the general formula (CDN2-e), L EP1 L EP2 and L EP3 Each can independently represent a single bond or a divalent linker. When n is 2 or more, there are multiple L's. EP2 They can be the same group or different groups.

[0153] In the general formula (CDN2-e), L is used as EP1 L EP2 and L EP3 The divalent linker represented can also be exemplified as L in the general formula (CDN1-e). EP Examples of preferred embodiments are listed using the divalent linking groups represented.

[0154] The polymer, which is a polymer of a compound represented by the general formula (CDN1), may be, for example, a polymer in which at least three or more compounds represented by the general formula (CDN1) are three-dimensionally cross-linked, with or without the help of linking groups. Examples of polymers in which compounds represented by the general formula (CDN1) are three-dimensionally cross-linked, include compounds represented by the following structural formulas.

[0155] [Chemical Formula 7]

[0156]

[0157] In the above structural formula, R 10 R 20 And P20 and R in general formula (CDN1) 1 R2 The meaning is the same as P2. L 10 Indicates a single bond or a divalent linkage group. Multiple R groups exist. 10 R 20 and L 10 These can be the same group or different groups. There can be a plurality of P20s, which can be the same number or different numbers.

[0158] In the above structural formula, as L 10 The divalent linking group represented can be, for example, an alkylene group that may have substituents (preferably an alkylene group with 2 or more and 30 or less carbon atoms, more preferably an alkylene group with 5 or more and 20 or less carbon atoms).

[0159] As a substituent mentioned above, another example can be found in R of the general formula (CDN1). 1 Substituents listed in the table are substituents.

[0160] The compounds represented by the above structural formulas can be further modified, for example, by epoxidation. Specifically, it can be a compound in which the hydroxyl groups of the compound represented by the above structural formulas are replaced by groups (EP), such as a compound represented by the following structural formula, namely a polymer of a compound represented by the general formula (CDN1-e) through three-dimensional cross-linking polymerization.

[0161] [Chemical Formula 8]

[0162]

[0163] In the above structural formula, R 10 R 20 And P20 and R in the general formula (CDN1-e) 1 R 2 The meaning is the same as P2. L 10 Indicates a single bond or a divalent linkage group. Multiple R groups exist. 10 R 20 and L 10 These can be the same group or different groups. There can be a plurality of P20s, which can be the same number or different numbers.

[0164] In the above structural formula, as L 10 The divalent linking group represented can be, for example, an alkylene group that may have substituents (preferably an alkylene group with 2 or more and 30 or less carbon atoms, more preferably an alkylene group with 5 or more and 20 or less carbon atoms).

[0165] As a substituent mentioned above, another example can be found in R of the general formula (CDN1). 1Substituents listed in the table are substituents.

[0166] From the viewpoint of improving the transparency of the resin molded article, the cashew nut compound preferably includes, for example, a cashew nut compound having an epoxy group, and more preferably a cashew nut compound having an epoxy group.

[0167] Commercially available cashew nutshell compounds can be used. Examples of commercially available cashew nutshell compounds include NX-2024, Ultra LITE 2023, NX-2026, GX-2503, NC-510, LITE 2020, NX-9001, NX-9004, NX-9007, NX-9008, NX-9201, NX-9203 manufactured by Cardolite, and LB-7000, LB-7250, and CD-5L manufactured by TOHOKU CHEMICAL INDUSTRIES, LTD. Commercially available cashew nutshell compounds with epoxy groups include NC-513, NC-514S, NC-547, LITE513E, and Ultra LTE 513 manufactured by Cardolite.

[0168] From the viewpoint of improving the biodegradation rate of the resin molded article, the hydroxyl value of the cashew nut shell compound is preferably 100 mg KOH / g or more, more preferably 120 mg KOH / g or more, and even more preferably 150 mg KOH / g or more. The hydroxyl value of the cashew nut shell compound is measured according to Method A of ISO 14900.

[0169] When using a cashew nut compound with an epoxy group, from the viewpoint of improving the transparency of the resin molded article, its epoxy equivalent is preferably 300 or more and 500 or less, more preferably 350 or more and 480 or less, and even more preferably 400 or more and 470 or less. The epoxy equivalent of the cashew nut compound with an epoxy group is measured according to ISO 3001.

[0170] From the viewpoint of improving the biodegradation rate of the resin molded article, the molecular weight of the cashew phenol compound is preferably 250 or more and 1000 or less, more preferably 280 or more and 800 or less, and even more preferably 300 or more and 500 or less.

[0171] Cashew phenol compounds can be used alone or in combination with two or more.

[0172] The ratio (B / A) of the plasticizer content (B) to the biodegradable resin content (A) is preferably 0.02 or more and 0.9 or less, more preferably 0.05 or more and 0.85 or less, and even more preferably 0.1 or more and 0.8 or less.

[0173] For example, by setting the plasticizer content within the above range, it is easier to improve the flexibility of the resin particles, which is therefore preferred.

[0174] -Other ingredients-

[0175] Other components may be contained in the parent particle.

[0176] Other components include, for example, flame retardants, compatibilizers, anti-sticking agents, lightfastness agents, weathering agents, colorants, pigments, modifiers, anti-drip agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fiber, carbon fiber, talc, clay, mica, glass flakes, cullet, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid-receptor agents for preventing acetic acid release (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc, etc.), and reactive scavengers (e.g., epoxy compounds, acid anhydride compounds, carbodiimide, etc.).

[0177] The content of other components relative to the total amount of parent particles is preferably 0% by mass or more and 5% by mass or less. Here, "0% by mass" means that no other components are included.

[0178] The parent material may contain resins other than biodegradable resins. However, when other resins are included, their content relative to the total amount of parent material should be, for example, less than 5% by mass, and preferably less than 1% by mass. More preferably, no other resins are contained (i.e., 0% by mass).

[0179] Other resins include, for example, conventionally known thermoplastic resins, specifically, polycarbonate resins; polypropylene resins; polyester resins; polyolefin resins; polyester carbonate resins; polyphenylene ether resins; polyphenylene sulfide resins; polysulfone resins; polyethersulfone resins; polyaryl resins; polyetherimide resins; polyacetal resins; polyvinyl alcohol acetal resins; polyketone resins; polyetherketone resins; polyetheretherketone resins; polyaryl ketone resins; polyether nitrile resins; liquid crystal resins; polybenzimidazole resins; polyurethane resins; and resins selected from aromatic olefins. Vinyl polymers or copolymers obtained by polymerization or copolymerization of one or more vinyl monomers from the group consisting of vinyl compounds, methacrylates, acrylates, and ethylene cyanide compounds; diene-aromatic alkenyl compound copolymers; ethylene cyanide-diene-aromatic alkenyl compound copolymers; aromatic alkenyl compound-diene-ethylene cyanide-N-phenylmaleimide copolymers; ethylene cyanide-(ethylene-diene-propylene (EPDM))-aromatic alkenyl compound copolymers; vinyl chloride resins; vinyl chloride resins, etc. These resins can be used alone or in combination of two or more.

[0180] (Floor 1 and Floor 2)

[0181] The resin particles involved in this embodiment preferably have, for example, a first layer comprising at least one cationic resin selected from polyalkyleneimide, polyacrylamide, and polyethyleneamine, and a second layer comprising anionic or nonionic hydrophobic compounds on the surface of the parent particle.

[0182] By having the first layer and the second layer, even in the event of plasticizer leakage from the parent particle, the plasticizer is easily retained between the parent particle surface and the first and second layers. Therefore, the leakage of plasticizer from the resin particle is suppressed. Thus, by having the first layer and the second layer, resin particles that are further suppressed from leakage are more easily formed.

[0183] -Level 1-

[0184] The first layer is a resin layer present on the surface of the parent particle. Furthermore, the first layer comprises at least one cationic resin selected from polyalkyleneimide, polyacrylamide, and polyethyleneimine.

[0185] The cationic resin can be any of polyalkylene imide, polyacrylamide, and polyethyleneimine, but from the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, polyalkylene imide is preferred, for example.

[0186] From the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, polyalkylene imides are preferred, for example, those having structural units having alkylene groups having 1 or more and 6 or less carbon atoms (preferably 1 or more and 4 or less carbon atoms, more preferably 1 or more and 2 or less carbon atoms), and polyethyleneimine is even more preferred.

[0187] Polyethyleneimine, in particular, is a compound with high adhesiveness and high water absorption. This is because the amino and hydroxyl groups of polyethyleneimine are hydrogen-bonded, ion-bonded with carboxyl groups, and covalently bonded with carbonyl groups. Furthermore, polyethyleneimine possesses both polar groups (amino) and hydrophobic groups (vinyl) in its structure, thus exhibiting the property of readily bonding with different substances.

[0188] Furthermore, polyethyleneimine is a highly cationic compound. Therefore, polyethyleneimine exists in water in a polycationic form and neutralizes and adsorbs anionic substances.

[0189] Furthermore, polyethyleneimine possesses highly reactive primary or secondary amine groups, making it a highly reactive compound. Consequently, it readily reacts with a wide variety of compounds.

[0190] Therefore, as a polyalkylene imide, if polyethyleneimine is used, the second layer containing the aqueous compound is more firmly coated by the parent particle, thus having a biodegradation rate that varies over time, and the initial biodegradation rate tends to slow down.

[0191] From the viewpoint that the rate of biodegradation increases over time and the initial rate of biodegradation decreases, the number average molecular weight of the cationic resin is preferably 300 or more and 100,000 or less, more preferably 10,000 or more and 85,000 or less, and even more preferably 50,000 or more and 80,000 or less.

[0192] The number-average molecular weight of the cationic resin was measured using tetrahydrofuran and converted to polystyrene by gel permeation chromatography (GPC apparatus: TOSOH CORPORATION, HLC-8320GPC, column: TSKgelα-M).

[0193] -Level 2-

[0194] The second layer is a compound layer present on top of the first layer. Furthermore, the second layer contains anionic or nonionic compounds or hydrophobic compounds.

[0195] Examples of anionic or nonionic compounds or hydrophobic compounds include hydrophobic compounds with anionic groups (-COOH (carboxyl group), -SO3H (sulfone group), etc.) and hydrophobic compounds without cationic or anionic groups.

[0196] Furthermore, the term "water-degradable compound" refers to a compound that imparts water degradability (specifically, water contact angle) to the biodegradable resin particles described later.

[0197] Examples of aqueous compounds include silicone compounds, hydrocarbon compounds, fatty acid compounds, acrylic resins, polyester resins, and urethane resins.

[0198] From the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, it is preferably selected from at least one of the group consisting of silicone compounds, hydrocarbon compounds, fatty acid compounds, acrylic resins, polyester resins and urethane resins.

[0199] Examples of silicone compounds include dimethyl polysiloxane, methyl polysiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, cyclopolymethylsiloxane, various modified silicone oils (alkyl-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, fluorine-modified silicone oil, amino-modified silicone oil, etc.), MQ resin, and silicone rubber.

[0200] Among them, from the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, the silicone compound is preferably selected from at least one of the group consisting of dimethyl polysiloxane, methyl polysiloxane, MQ resin and silicone rubber.

[0201] Here, MQ resin refers to a silicone resin having a monofunctional siloxane unit [(CH3)3SiO1 / 2], i.e., the M unit, and a tetrafunctional siloxane unit [SiO4 / 2], i.e., the Q unit.

[0202] Commercially available silicone compounds include those manufactured by Shin-Etsu Chemical Co., Ltd. (KM-902, KM-903, KM-910, KM-9729, POLON-MN-ST, KM-9737A, KM-9782, KM-9738A, KM-752T, POLON-MF-33, KM-9717, X-51-1302M (MQ resin), POLON-MF-56, KM-2002-L-1, KM-2002-T, KM-9772, KM-9749, POLON-MF-40, KM-9729, X-52-1133, etc.) and those manufactured by Wacker Asahikasei SiliconeCo., Ltd. (BELSIL DM3112VP).

[0203] Examples of hydrocarbon compounds include petroleum waxes (paraffin wax, microcrystalline wax, petrolatum wax, etc.) and synthetic hydrocarbon waxes (polyethylene wax, polypropylene wax, polybutene wax, Fischer-Tropsch synthetic wax, etc.).

[0204] From the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, the hydrocarbon compound is preferably selected from at least one of the group consisting of paraffin wax, microcrystalline wax, polyethylene wax, and polypropylene wax.

[0205] Commercially available hydrocarbon compounds include microcrystalline wax (EMUSTAR-0001, etc.) manufactured by NIPPON SEIRO CO.,LTD., paraffin wax (EMUSTAR-0135, etc.) manufactured by NIPPON SEIRO CO.,LTD., paraffin wax (AQUACER497, etc.) manufactured by BYK, polyethylene wax (AQUACER507, AQUACER840, AQUACER1547, AQUACER272, etc.) manufactured by BYK, polyethylene wax (HITEC E-2213, HITEC E-6324, etc.) manufactured by TOHO Chemical Industry Co.,Ltd., polypropylene wax (AQUACER593, etc.) manufactured by BYK, and polypropylene (HITEC P-9018, HITEC P-5060P, etc.) manufactured by TOHO Chemical Industry Co.,Ltd.

[0206] Examples of fatty acid compounds include vegetable oils containing fatty acids (castor oil, tung oil, linseed oil, shortening, corn oil, soybean oil, sesame oil, rapeseed oil, sunflower oil, rice bran oil, camellia oil, coconut oil, palm oil, walnut oil, olive oil, peanut oil, almond oil, jojoba oil, cocoa butter, shea butter, neem oil, safflower oil, wood wax, candelilla wax, rice bran wax, carnauba wax, etc.).

[0207] From the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, it is preferably selected from at least one of the group consisting of carnauba wax, rice bran wax, candelilla wax, palm wax, castor oil wax, soybean oil wax and sunflower oil wax.

[0208] Commercially available fatty acid compounds include canopy wax (EMUSTAR-0413 (Brazilian carnauba wax)) manufactured by NIPPON SEIRO CO.,LTD., rice bran wax (AQUASPROUT-7300, etc.) manufactured by NIPPON SEIRO CO.,LTD., palm wax (AQUASPROUT-7100, etc.) manufactured by NIPPON SEIRO CO.,LTD., castor oil wax (AQUASPROUT-7500, etc.) manufactured by NIPPON SEIRO CO.,LTD., soybean oil wax (AQUASPROUT-7200, etc.) manufactured by NIPPON SEIRO CO.,LTD., sunflower oil wax (AQUASPROUT-7400, etc.) manufactured by NIPPON SEIRO CO.,LTD., and palm oil wax (kakkokasei TKE, etc.) manufactured by NIPPON SEIRO CO.,LTD., etc.

[0209] Examples of acrylic resins include polymers of acrylic acid and polymers of alkyl acrylates.

[0210] Commercially available acrylic resins include, for example, those manufactured by TAISEI FINE CHEMICAL CO,.LTD. (3WX-2015, 3MF-320, 3MF-333, 3MF-407, etc.) and those manufactured by DIC CORPORATION (KOTE SFC-6440, BONKOTE CE-6270, BONKOTE CE-6400, BONKOTE CF-2800, etc.).

[0211] Examples of polyester resins include condensation polymers of polycarboxylic acids and polyols, and ring-opening condensation polymers of cyclic lactams.

[0212] Commercially available polyester resins include, for example, polyester resins manufactured by Takamatsu Oil & Fat Co., Ltd. (A-110F, A-160P, A-520, A-613D, A-615GE, A-640, A-645GH, A-647GEX, etc.).

[0213] Examples of urethane resins include polyester polyurethanes, polyether polyurethanes, and polycarbonate polyurethanes. Furthermore, materials in which a urethane polymer shell surrounds the core of a propylene polymer fiber can also be used as urethane resins.

[0214] Commercially available urethane resins include, for example, those manufactured by TAISEI FINE CHEMICAL CO,.LTD. (WEM-031U, WEM-200U, WEM-321U, WEM-3000, WBR-016U, WBR-2101, etc.).

[0215] -Content of each layer-

[0216] In the biodegradable resin particles involved in this embodiment, from the viewpoint of increasing biodegradation rate over time and decreasing initial biodegradation rate, the mass ratio of the amount of cationic resin coating in the first layer to the amount of aqueous compound coating in the second layer (the amount of cationic resin coating / the amount of aqueous compound coating) is preferably 0.05 or more and 20 or less, more preferably 0.1 or more and 10 or less, and even more preferably 0.1 or more and 3 or less.

[0217] Furthermore, from the viewpoint that the biodegradation rate increases over time and the initial biodegradation rate decreases, the content of cationic resin relative to the parent particles is preferably 0.05% by mass or more and 15% by mass or less, more preferably 0.1% by mass or more and 10% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.

[0218] Furthermore, from the viewpoint that the biodegradation rate increases over time and the initial biodegradation rate decreases, the content of the aqueous compound relative to the parent particle is preferably 0.05% by mass or more and 15% by mass or less, more preferably 0.1% by mass or more and 10% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.

[0219] Here, the coating amounts of the cationic resin and the aqueous compound (i.e., the coating amounts of the first and second layers) are measured as follows. The coating amount of the cationic resin is determined by the difference between the amount of cationic resin processed and the amount of cationic resin obtained by drying and curing the treated supernatant. Similarly, the coating amount of the aqueous compound is determined by the difference between the amount of aqueous compound processed and the amount of aqueous compound obtained by drying and curing the treated supernatant.

[0220] <Characteristics of Resin Particles>

[0221] (particle size)

[0222] The volume average particle size of the resin particles is preferably 3 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and even more preferably 8 μm or more and 60 μm or less.

[0223] The particle size distribution index GSDv of the large diameter side number of biodegradable resin particles is preferably 1.5 or less, more preferably 1.3 or less, and even more preferably 1.2 or less.

[0224] The following measures the volume average particle size and the number of large diameter particles in the biodegradable resin particles, as well as the particle size distribution index GSDv.

[0225] The particle size was measured using the Beckman Coulter LS13 320 (BECKMAN COULTER) particle size distribution measurement device. The cumulative distribution of the particle size was plotted from the small diameter side with a volume reference, and the particle size that constituted the cumulative 50% was determined as the volume average particle size.

[0226] On the other hand, describing the cumulative distribution of particle size on the small-diameter side using a volumetric criterion, the particle size that accounts for the cumulative 50% is defined as the number average particle size D50v, and the particle size that accounts for the cumulative 84% is defined as the number particle size D84v. Furthermore, the number particle size distribution index GSDv on the large-diameter side is given by the formula GSDv = (D84v / D50v).1 / 2 calculate.

[0227] (Specific amount of elements)

[0228] The amount of a metal element (specific metal element) whose ion valence may be 2 or higher as determined by X-ray fluorescence analysis is 0.002% by mass or more and 2.0% by mass or less relative to the total amount of resin particles.

[0229] The amount of a specific metallic element is measured in the following order.

[0230] Using an X-ray fluorescence analyzer (Shimadzu Corporation, XRF1500), with X-ray output at 40V and 70mA, the area was measured. Qualitative and quantitative analyses were performed under a 15-minute measurement period. All elements present in the measurement area were analyzed. The atomic weights of all elements and the specific metal element present in the measurement area were calculated. Then, the atomic weights of all elements and the specific metal element were converted to mass. Furthermore, the percentage of the mass of the specific metal element relative to the mass of all elements present in the measurement area was calculated and set as the amount of the specific metal element determined by X-ray fluorescence analysis.

[0231] From the viewpoint of resin particles designed to maintain flexibility and further suppress exudation during long-term storage under high-temperature conditions, the amount of a specific metal element determined by X-ray fluorescence analysis relative to the total amount of resin particles is preferably 0.02% by mass or more and 1.5% by mass or less, more preferably 0.1% by mass or more and 1.2% by mass or less, and even more preferably 0.2% by mass or more and 1.0% by mass or less.

[0232] As for specific elements, there are no special restrictions as long as the ionic valence of a metal element is likely to be 2 or higher. Examples include metal elements in Group 2 of the periodic table such as Mg and Ca; metal elements in Group 12 of the periodic table such as zinc; metal elements in Group 13 of the periodic table such as Al; metal elements in Group 14 of the periodic table such as Si; and transition metal elements such as Fe, Ti, and Zr.

[0233] The specific metallic element is preferably at least one selected from the group consisting of Ca, Mg, Al and Fe, and more preferably Ca.

[0234] Among specific metallic elements, Ca, Mg, Al, and Fe more readily bond with the functional groups of biodegradable resins. Therefore, resin particles are more likely to possess cross-linked structures. Ca, with its larger ionic radius, is particularly advantageous in bonding with the functional groups of biodegradable resins. Consequently, it is more likely to produce resin particles that maintain flexibility and suppress exudation during long-term storage at high temperatures.

[0235] (Rs / Rp)

[0236] The ratio (Rs / Rp) of the equivalent circular diameter Rs of the aggregate to the equivalent circular diameter Rp of the primary particle after storage for three months at 50℃ and 50%RH is less than 1.5.

[0237] From the viewpoint of further suppressing leakage during long-term storage under high temperature conditions, the ratio (Rs / Rp) is preferably 1.4 or less, more preferably 1.3 or less, and even more preferably 1.2 or less.

[0238] The lower limit of the ratio (Rs / Rp) is preferably 1.0 or higher, for example.

[0239] The following calculations are performed on the circular equivalent diameter Rs of the aggregate and the circular equivalent diameter Rp of the primary particles.

[0240] First, the resin particles were stored in a chamber at 50°C and 50% humidity for three months. After storage, the aggregates present in the resin particles were observed and images were taken using a scanning electron microscope (SEM) (Hitachi, Ltd., S-4100), and the images were read by an image analysis device (LUZEX III, Nirecocorporation). The area of ​​each aggregate was measured using image analysis, and the equivalent circular diameter was calculated from this area value. The equivalent circular diameter of each aggregate was calculated for 100 aggregates. The arithmetic mean of the equivalent circular diameters calculated from the 100 aggregates was taken as the equivalent circular diameter Rs of the aggregate. Furthermore, the equivalent circular diameter Rp of the primary particles present in the resin particles after storage was also calculated in the same order as the equivalent circular diameter Rs of the aggregates.

[0241] Here, the following method is used to determine the aggregates and primary particles present in the resin particles after storage. In images obtained by observing the stored resin particles using a SEM device, a single resin particle is defined as a primary particle. An area where two or more resin particles are in contact is defined as an aggregate.

[0242] (Hardness measurement)

[0243] The hardness is less than 75.

[0244] From the viewpoint of further improving flexibility, the indicated hardness is preferably 30 or more and 74 or less, more preferably 40 or more and 70 or less, and even more preferably 50 or more and 65 or less.

[0245] The hardness is determined as follows.

[0246] Resin particles were heated at 200°C and molded into a 2mm thick disc. The resulting disc was used as the measurement object, and a type D hardness tester was used to measure the hardness under a 5000g load. The hardness measurement was performed according to JISK 7215:1986.

[0247] <Method for manufacturing resin particles>

[0248] Examples of methods for manufacturing resin particles include the following.

[0249] (1) Mixing and crushing the components, crushing the resulting mixture and classifying it to obtain granular material;

[0250] (2) A dry method of obtaining granules by changing the shape of granules obtained by mixing and pulverizing through mechanical impact or heat.

[0251] (3) Mix the particle dispersion of each component, so that the particles in the dispersion aggregate and are heated and fused together to obtain the particle aggregation and fusion method.

[0252] (4) The organic solvent in which each component is dissolved is suspended in an aqueous solvent to produce granules containing each component by dissolution and suspension method.

[0253] (5) The components and binder are mixed and extruded to form granules. The granules are obtained by stirring in a solvent that dissolves only the binder. This is a mixing and dissolving method for granulation.

[0254] From the viewpoint that the amount of a specific metal element determined by X-ray fluorescence analysis is 0.002% by mass or more and 2.0% by mass or less relative to the total amount of resin particles, the method described above (4) is preferred as a method for manufacturing resin particles.

[0255] In the manufacture of resin particles based on the above (4) method, for example, it is preferable to pre-dissolve a metal element source containing a specific metal element in an aqueous solvent before suspending the organic solvent in which each component is dissolved in the aqueous solvent.

[0256] Examples of sources of metal elements include carbonates and hydroxides containing specific metal elements.

[0257] Examples of carbonates containing specific metallic elements include calcium carbonate, magnesium carbonate, aluminum carbonate, and iron carbonate.

[0258] Examples of hydroxides containing specific metallic elements include calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and iron hydroxide.

[0259] The content of the metal element source in the aqueous solvent relative to the total aqueous solvent is preferably 1% by mass or more and 20% by mass or less, more preferably 2% by mass or more and 15% by mass or less, and even more preferably 3% by mass or more and 10% by mass or less.

[0260] Methods for manufacturing resin particles having the first layer and the second layer can be exemplified by the following methods.

[0261] -Step 1-

[0262] In the first step, the mother particle is prepared.

[0263] The manufacturing methods of the parent particles can be exemplified by the manufacturing methods of the resin particles (1) to (5).

[0264] Next, an aqueous dispersion of the obtained parent particles is prepared. Before preparing the aqueous dispersion, the parent particles are preferably acid-washed, for example.

[0265] Next, an aqueous dispersion and an aqueous solution containing the dispersed parent particles and a cationic resin are mixed. Thereby, for example, the hydroxyl groups of the resin contained in the parent particles react with the amine sites of the cationic resin to form a first layer.

[0266] -Step 2-

[0267] In the second step, the masterbatch particles with the first layer formed are removed from the mixture. The removal of the masterbatch particles is carried out, for example, by filtering the mixture. The removed masterbatch particles are preferably washed with water, for example. This removes unreacted cationic resin.

[0268] Next, after preparing an aqueous dispersion containing the parent particles, the aqueous dispersion is mixed with a latex solution of anionic or nonionic aqueous compound. Thus, the latex of the aqueous compound is adsorbed onto the first layer of the parent particles.

[0269] Then, if the mixture is dried, the latex of the aqueous compound is destroyed, and the aqueous compound is film-formed on the first layer. Thus, the second layer is formed.

[0270] Through the above processes, the resin particles involved in this embodiment are obtained.

[0271] <Uses>

[0272] Examples of uses for the resin particles involved in this embodiment include cosmetic substrates, rolling materials, abrasives, washing agents, display pads, bead forming materials, light diffusing particles, resin reinforcing agents, refractive index control agents, biodegradation promoters, fertilizers, water-absorbing particles, toner particles, and granular particles that prevent adhesion.

[0273] Example

[0274] The following describes embodiments, but the present invention is not limited to these embodiments in any way. Furthermore, unless otherwise specified, "parts" and "%" in the following description refer to mass.

[0275] <Preparation of materials>

[0276] The following materials have been prepared.

[0277] [Biodegradable resins]

[0278] •CAB: Eastman Chemical "CAB381-20", cellulose acetate butyrate, weight average degree of polymerization 890, degree of acetyl substitution 1.05, degree of butyryl substitution 1.74.

[0279] •CAP: Eastman Chemical "CAP482-20", cellulose acetate propionate, weight average degree of polymerization 716, degree of acetyl substitution 0.18, degree of propionyl substitution 2.49.

[0280] PLA: Polylactic acid, weight-average molecular weight 180,000.

[0281] •PBS: Polybutylene succinate, weight average molecular weight 200,000.

[0282] •DAC: Daicel Corporation. "L-50", cellulose diacetate, weight average degree of polymerization 570.

[0283] •TAC: Daicel Corporation. Produces "LT-35", cellulose triacetate, with a weight-average degree of polymerization of 385.

[0284] [Plasticizer]

[0285] ·DIBA: diisobutyl adipate

[0286] ATBC: O-Tributyl Citrate

[0287] CDN: Cardolite "NX-2503", hydroxyethylated cashew nut shell powder, molecular weight 296-320

[0288] [Catonic resin in layer 1]

[0289] PEI: Polyethyleneimine, number average molecular weight 70,000

[0290] PAA: Polyacrylamide, number average molecular weight 25,000

[0291] PVAM: Polyvinylamine, number average molecular weight 100,000

[0292] [Anionic or nonionic hydrophilic compounds in the second layer]

[0293] ·EMUSTAR-0413: Canopa wax manufactured by NIPPON SEIRO CO.,LTD., anionic

[0294] ·EMUSTAR-0136: Paraffin wax manufactured by NIPPON SEIRO CO.,LTD., nonionic.

[0295] [Examples 1-11, 14-21, Comparative Examples 1, 2, 4-6]

[0296] (Preparation of resin particles)

[0297] The temperature of the barrel was adjusted according to the addition ratios shown in Table 1, and the mixture was kneaded using a twin-shaft mixing unit (manufactured by SHIBAURA MACHINE CO., LTD., TEX 41SS) to obtain a granular resin composition (hereinafter referred to as resin granules).

[0298] (Production of resin particles)

[0299] 300g of resin particles were completely dissolved in 700g of methyl ethyl ketone. This solution was then added to an aqueous solution containing 50g of the metal element source shown in Table 1, dispersed in 500g of pure water, and stirred for 3 hours. Next, it was added to an aqueous solution containing 4g of carboxymethyl cellulose and 200g of methyl ethyl ketone, dispersed in 600g of pure water, and stirred in a high-speed emulsifier for 5 minutes. 10g of sodium hydroxide was added, and the mixture was heated to 80°C and stirred for 3 hours to remove the methyl ethyl ketone. Then, 10g of dilute hydrochloric acid was added to dissolve the metal element source. After filtering the residue, the solid component was freeze-dried to obtain the resin particles.

[0300] [Examples 12, 13, 22-24, Comparative Example 3]

[0301] (Preparation of resin particles)

[0302] The temperature of the barrel was adjusted according to the addition ratios shown in Table 1, and the mixture was kneaded using a twin-shaft mixing unit (manufactured by SHIBAURA MACHINE CO., LTD., TEX 41SS) to obtain a granular resin composition (hereinafter referred to as resin granules).

[0303] (The creation of the mother particle)

[0304] 300g of resin particles were completely dissolved in 700g of methyl ethyl ketone. This solution was then added to an aqueous solution containing 50g of the metal element source shown in Table 1, dispersed in 500g of pure water, and stirred for 3 hours. Next, it was added to an aqueous solution containing 4g of carboxymethyl cellulose and 200g of methyl ethyl ketone, dispersed in 600g of pure water, and stirred in a high-speed emulsifier for 5 minutes. 10g of sodium hydroxide was added, and the mixture was heated to 80°C and stirred for 3 hours to remove the methyl ethyl ketone. Then, 10g of dilute hydrochloric acid was added to dissolve the metal element source. After filtering the residue, the mixture was redispersed in pure water to obtain a slurry of mother particles.

[0305] (Production of resin particles)

[0306] Biodegradable resin particles were obtained using the materials of the first and second layers shown in Table 1 in the following manner.

[0307] 500 parts of a slurry with a 20% solids content were prepared. For the solids content (100 parts) of this slurry, the cationic resin solution was added in the amounts shown in Table 1 (converted to purity), and the mixture was stirred at 25°C for 1 hour. After stirring, the residue was filtered, redispersed in pure water, and 500 parts of a slurry with a 20% solids content were prepared. For the solids content (100 parts) of this slurry, the aqueous compound was added in the amounts shown in Table 1 (converted to purity), and the mixture was stirred at 25°C for 1 hour. After stirring, the residue was filtered, and the solids were freeze-dried to obtain biodegradable resin particles.

[0308] Through the above processes, biodegradable resin particles were obtained.

[0309] <Evaluation>

[0310] Following the described method, the amount of metal elements with ionic valences greater than 2, as determined by X-ray fluorescence analysis ("Metal Element Amount" in the table), the number-average particle size D50v, the indicated hardness, and the ratio (Rs / Rp) of the circumspherical equivalent diameter Rs of the aggregates to the circumspherical equivalent diameter Rp of the primary particles after storage at 50°C and 50% RH for three months were measured in the obtained resin particles. The results are shown in Table 2.

[0311] (Flexibility Evaluation)

[0312] The flexibility of the resin particles was evaluated using the measured hardness values ​​and according to the evaluation criteria described below. The results are shown in Table 2.

[0313] -Evaluation Criteria-

[0314] G1(〇): Indicated hardness ≤65

[0315] G2(△): 65 < indicated hardness < 75

[0316] G3(×): 75≤Indicated Hardness

[0317] (Evaluation of long-term thermal storage performance)

[0318] The long-term thermal storage properties of the resin particles were evaluated using the calculated ratio (Rs / Rp) and according to the evaluation criteria below. The results are shown in Table 2.

[0319] -Evaluation Criteria-

[0320] G1(〇): Ratio (Rs / Rp) ≤ 1.2

[0321] G2(△): 1.2 < ratio (Rs / Rp) < 1.5

[0322] G3(×): 1.5 ≤ Rs / Rp

[0323] [Table 1]

[0324]

[0325] [Table 2]

[0326]

[0327] As can be seen from the above results, the resin particles in this embodiment are resin particles that maintain flexibility and suppress exudation during long-term storage under high temperature conditions.

[0328] The embodiments of the present invention described above are provided for illustrative purposes. Furthermore, these embodiments do not encompass the entirety of the invention, nor do they limit the invention to the disclosed methods. It will be apparent to those skilled in the art that various modifications and variations will be readily understood. These embodiments were chosen and described to most readily explain the principles and applications of the invention. Thus, those skilled in the art can understand the invention through various modifications that are assumed to be optimized for specific uses of various embodiments. The scope of the invention is defined by the foregoing claims and their equivalents.

Claims

1. A resin particle comprising a parent particle containing a biodegradable resin and a plasticizer, wherein, The biodegradable resin is a cellulose acylate or a polyester. It includes metallic elements with an ionic valence of 2 or higher as specific metallic elements. X-ray fluorescence analysis determined that the amount of the specific metal element relative to the total amount of resin particles was greater than 0.002% by mass and less than 2.0% by mass. The metal source of the specific metal element is a carbonate or hydroxide containing the metal element. The ratio (B / A) of the content of the plasticizer (B) to the content of the biodegradable resin (A) is 0.1 or more and 0.8 or less.

2. The resin particles according to claim 1, wherein, The metallic element with an ionic valence of 2 or higher includes at least one selected from the group consisting of Ca, Mg, Al and Fe.

3. The resin particles according to claim 2, wherein, The metal elements with an ionic valence of 2 or higher include Ca.

4. The resin particles according to claim 1, wherein, The cellulose acylate is at least one selected from the group consisting of cellulose diacetate, cellulose acetate propionate, and cellulose acetate butyrate.

5. A resin particle comprising a master particle containing a biodegradable resin selected from cellulose acylates or polyesters and a plasticizer, wherein, It includes metallic elements with an ionic valence of 2 or higher as specific metallic elements. The metal source of the specific metal element is a carbonate or hydroxide containing the metal element. After being stored at 50℃ and 50%RH for three months, the ratio of the equivalent circular diameter Rs of the aggregates to the equivalent circular diameter Rp of the primary particles (Rs / Rp) is less than 1.

5. The hardness is less than 75. The ratio (B / A) of the content of the plasticizer (B) to the content of the biodegradable resin (A) is 0.1 or more and 0.8 or less.

6. The resin particle according to any one of claims 1 to 5, wherein the surface of the parent particle sequentially comprises: The first layer comprises at least one cationic resin selected from polyalkyleneimide, polyacrylamide, and polyethyleneimine; and The second layer contains anionic or nonionic hydrophilic compounds.

Citation Information

Patent Citations

  • Preparation process of covered particle

    JP2004210848A

  • Biodegradable resin composition

    JP2012077245A

  • Resin composition and resin molded article

    CN110872394A

  • Plasticizer for biodegradable resin

    CN1872902A

  • Cellulose material

    JP2004256579A